Shoulder dystocia, a rare complication of ruptured uterus: a case report and review - Aditya, Vani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Shoulder dystocia is one of the most difficult complications of labor that is often unpredictable and hence unpreventable. In most cases, the cause is dystocia from the bony pelvis. The major brunt of complications is borne by the fetus. In neglected cases, grave maternal complications like obstructed labor and rupture of uterus may result. Very rarely, the reverse, uterine rupture leading to shoulder dystocia can also occur. The dystocia results from the soft tissue of the ruptured uterus itself. The present case is reported to emphasize the importance of early recognition of this condition. A gravida 3 para 2 woman presented in obstetrics emergency with delivery of head at home, six hours back, after being in labor for 8 to 10 hours. The uterine contractions ceased immediately following the delivery of the head. Her first delivery was by cesarean that was done for fetal distress. Second was an uneventful vaginal delivery at home. In this pregnancy, she presented with ruptured uterus .On laparotomy, the rupture was seen to involve the previous uterine scar. Lower segment was thick and previous uterine incision although transverse was situated higher up, above the lower segment. Rupture was repaired and patient recovered without any complications. In women with risk factors for uterine rupture, delivery should be conducted at hospitals with facilities for emergency cesarean. In this high risk group, if shoulder dystocia occurs, rupture of the uterus must be suspected as an underlying cause. Routine management protocols must be abandoned in favor of urgent laparotomy to improve the chances of fetal survival and save from litigation. At the same time, this case should not deter us from trial of labor after caesarean.